Serum levels of AFP and CA19-9 after Intraoperative Radiotherapy Combined with Drug Therapy on Liver and Pancreatic Tumors: Serum levels of AFP and CA19-9 in Liver and Pancreatic Tumors - Jia, Xin; Jiang, Zongliang (Journal of Medical Biochemistry, 2025)
Objective To explore the efficacy of intraoperative radiotherapy combined with drug therapy on serum levels of AFP and CA19-9 for liver and pancreatic tumors to provide more effective treatment strategies for clinical practice. Method A retrospective analysis was conducted on 190 patients with liver and pancreatic tumors who underwent surgical resection combined with intraoperative radiotherapy in the hospital from March 2023 to September 2024. The patients were segmented into an experimental group (intraoperative radiotherapy combined with drug therapy, n=95) and a control group (traditional treatment, n=95) at random. The experimental group accepted IORT, targeted drugs, and immunomodulators after surgical resection. The control group received surgical resection and chemotherapy or external radiation therapy. The main observation indicators include tumor marker levels, biochemical indicators, recurrence rate, survival rate, quality of life, postoperative complications, pain score, and psychological status. Results The levels of AFP and CA19-9 in the experimental group decreased by 16.2 ng/mL and 74.7 U/mL, which surpassed those in the control group (P<0.05). After treatment, the liver function indicators of the experimental group significantly improved (ALT decreased from 32.1 ± 12.5 U/L to 22.4 ± 10.1 U/L, P=0.00), and renal function also improved. The recurrence and metastasis rates in the experimental group were lower (P<0.05). Although there was no discrepancy in common adverse reactions, the experimental group had a lower incidence of adverse reactions in radiation dermatitis and infection (P<0.05). The survival curve demonstrated that the survival rate of the experimental group was higher (P<0.05). The quality of life assessment showed that the experimental group had improved scores in multiple dimensions such as physical function, role function, and emotional function (P<0.05). In correlation analysis, the decrease of tumor markers was significantly negatively correlated with the improvement of quality of life (R=-0.45, P=0.00). The improvement of biochemical indicators was negatively connected to the reduction of postoperative complications (R=-0.30, P=0.01). The pain scores of the control group were higher at all time points after treatment (P<0.05). Conclusion Intraoperative radiotherapy combined with drug therapy has shown outstanding efficacy in treating the liver and pancreatic tumors, effectively reducing tumor marker levels, improving liver and kidney function, reducing recurrence and metastasis rates, improving survival rates and life quality, while reducing postoperative complications and adverse reactions. This comprehensive treatment plan provides a new effective strategy for the treatment of liver and pancreatic tumors.